Temperature sensing in hyperthermia study in breast cancer treatment using optical fiber bragg gratings (2020)
This paper presents the simulation results of an optoelectronics temperature monitoring system intended to be used in a hyperthermia breast-cancer treatment. This treatment involves the use of electromagnetic fields in order to generate a concentrated heat pattern around tissues affected by cancer. Therefore, all-optical fiber sensors which are immune to electromagnetic signals should be used to determine the relationship between the applied electromagnetic power density and the actual temperature in the modeled tissue. The proposed optoelectronic system is an electro-optic dual-comb fiber Bragg grating interrogation system, which uses a simple architecture with a continuous wave laser and a Mach-Zehnder modulator at an specific bias voltage to generate additional modes around the central wavelength of the laser. The photo-detected response of the sensor at the modulation frequency makes it possible to read the changes in the sensor’s Bragg wavelength. In the simulation study, the modulation frequency of the Mach-Zehnder modulator was swept in order to find the best configuration in terms of amplitude temperature resolution.